A facile, green synthesis of carbon quantum dots from Polyalthia longifolia and its application for the selective detection of cadmium. (February 2023) - Sariga,; Ayilliath Kolaprath, Mrinalini Kalyani; Benny, Libina; Varghese, Anitha
Abstract: Carbon quantum dots (CQDs) has received world-wide recognition for their outstanding physicochemical properties that have the ability to substitute the semiconductor quantum dots. Herein, we have developed a strategy to determine the presence of Cd 2+ using CQDs as a fluorescence probe. The CQDs were synthesized from the leaves of Polyalthia longifolia (a natural source) through a one-step hydrothermal method. The CQDs obtained from Polyalthia longifolia (p-CQDs) was characterized using XRD, TEM, FTIR, Raman Spectroscopy, XPS Studies, UV–Visible spectroscopy and PL Spectroscopy. The p-CQDs displayed bright red fluorescence under the UV light, with good water solubility, and appreciable photostability and a quantum yield of 22%. The p-CQDs had a quasi-spherical morphology with an average particle size of 3.33 nm. The p-CQDs showed high selectivity and sensitivity for the detection of Cd 2+ with a low limit of detection of 2.4 nM and a wide linear range of 7.3 nM–12 μM. The PL intensity of the p-CQDs showed a quenching effect in presence of Cd 2+ and the mechanism of quenching was validated via fluorescence lifetime decay studies. We have also studied the effectiveness of the fluorescent probe developed for Cd 2+ sensing in real samples of ground water and industrial effluents. Graphical abstract: Image 1 Highlights: Green synthesis of carbon quantum dots (p-CQDs) via hydrothermal method. p-CQDs displayed bright red fluorescence, water solubility and photostability. Detection of Cd 2+ with high selectivity and sensitivity by fluorescence quenching. Nanomolar level of detection with wide linear dynamic range. Sensing of Cd 2+ in ground water and industrial effluents.